Promise Not To Tell - Krentz, Jayne Ann (New York : Berkley, 2018)
"A broken promise reveals a terrifying legacy in this electrifying novel from the New York Times bestselling author of When All the Girls Have Gone. A painter of fiery, nightmarish visions throws herself into the sea--but she'll leave some of her secrets behind... Seattle gallery owner Virginia Troy has spent years battling the demons that stem from her childhood time in a cult and the night a fire burned through the compound, killing her mother. And now one of her artists has taken her own life, but not before sending Virginia a last picture: a painting that makes Virginia doubt everything about the so-called suicide--and her own past. Like Virginia, private investigator Cabot Sutter was one of the children in the cult who survived that fire...and only he can help her now. As they struggle to unravel the clues in the painting, it becomes clear that someone thinks Virginia knows more than she does and that she must be stopped. Thrown into an inferno of desire and deception, Virginia and Cabot draw ever closer to the mystery of their shared memories--and the shocking fate of the one man who still wields the power to destroy everything they hold dear"--
Library Journal
Booklist
Kirkus Reviews
Publishers Weekly
Adult
Keywords: Private investigators -- Fiction; Women artists -- Fiction; Romantic suspense fiction; Mystery fiction